2020
DOI: 10.1037/cdp0000292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sexual/gender minority- and race-based enacted stigma on mental health and substance use in female assigned at birth sexual minority youth.

Abstract: Objective: People of color who are also sexual and gender minorities (SGM) experience forms of enacted stigma based on both their racial/ethnic identity and their SGM status. We set out to test the effects of enacted stigma specific to race/ethnicity and SGM identity on mental health and substance use problems among female assigned at birth (FAB) SGM of color. Method: Data come from a community-based sample of FAB SGM who also identified as racial/ethnic minorities (N = 352). The effects of racial discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 79 publications
2
34
1
Order By: Relevance
“…Minority stress theory has also been adapted to conceptualize health among transgender populations due to similar distal and proximal minority stress processes (Hendricks & Testa, 2012). In recent research, transgender participants have reported distal stressors, such as family rejection (Klein & Golub, 2016), harassment and discrimination (Su et al, 2016), victimization (e.g., physical and sexual abuse; Newcomb et al, 2020) and being denied a job or fired due to one's gender identity or expression (Sawyer et al, 2016). These distal stressors have been associated with high rates of suicidal thoughts and behaviors (Clements-Nolle et al, 2006;Virupaksha et al, 2016) anddepression (Su et al, 2016).…”
Section: Theoretical Understanding Of Suicidal Thoughts and Behaviors...mentioning
confidence: 99%
“…Minority stress theory has also been adapted to conceptualize health among transgender populations due to similar distal and proximal minority stress processes (Hendricks & Testa, 2012). In recent research, transgender participants have reported distal stressors, such as family rejection (Klein & Golub, 2016), harassment and discrimination (Su et al, 2016), victimization (e.g., physical and sexual abuse; Newcomb et al, 2020) and being denied a job or fired due to one's gender identity or expression (Sawyer et al, 2016). These distal stressors have been associated with high rates of suicidal thoughts and behaviors (Clements-Nolle et al, 2006;Virupaksha et al, 2016) anddepression (Su et al, 2016).…”
Section: Theoretical Understanding Of Suicidal Thoughts and Behaviors...mentioning
confidence: 99%
“…Research has shown that the experience of sexual orientation microaggression increases the risks of depression and anxiety among LGB individuals [ 7 , 11 , 12 , 13 , 14 ]. Microaggression may result in feelings of being hurt, offended, or frustrated, and their mental health may be further compromised [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, to examine the associations of sexual orientation microaggression with anxiety and depression as well as the mediating effect of self-identity disturbance on the association among young adult LGB individuals. Based on the results of previous studies [ 7 , 11 , 12 , 13 , 14 ], it was hypothesized that sexual orientation microaggression will be significantly associated with depression and anxiety among young adult LGB individuals (Hypothesis 1a). Given that victimization and homophobic bullying has been found to increase the risk of self-identity disturbance among gay and bisexual men in emerging adulthood [ 27 ] and that self-identity disturbance has been associated with mood problems [ 28 , 29 ], it was hypothesized that self-identity disturbance would mediate the associations of sexual orientation microaggression with anxiety and depression among young adult LGB individuals (Hypothesis 1b).…”
Section: Introductionmentioning
confidence: 99%
“…This theme is in line with broader research showing that Black, Indigenous, and People of Color (BIPOC) who also identify as SGM, face stigma toward multiple facets of their identity. Research has shown that enacted stigma, on the basis of race and SGM status, significantly predicts poorer mental health outcomes and higher risks for developing SU issues (Swann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%